Description of Myolepta pazukii Gilasian & Reemer sp. nov. (Diptera: Syrphidae) with notes on the Iranian species of Myolepta Newman - Gilasian, Ebrahim; Reemer, Menno; Parchami-Araghi, Mehrdad (Zootaxa, 2016)
Myolepta pazukii Gilasian & Reemer sp. nov. is described from Iran based on a single male specimen. Photographs of the male holotype and illustrations of its abdomen and hypandrium are provided. The new species is incorporated into the key to the west Palaearctic Myolepta species provided by Reemer et al. (2004). Taxonomic notes and distribution data on two recorded Iranian Myolepta species are presented.